Methylmercury-Induced Ferroptosis May Be Attenuated by Vitamin K in PC12 Cells - Yanli Lin (Proceedings)
Introduction: As a ubiquitous environmental pollutant, methylmercury (MeHg) induces toxic effects in the nervous system [...]